Structural Changes in Ashura Literary Works: From Epic to Tragedy and Elegy - Mohammad-Reza Javadi-Yeganeh (Religion & Communication, 2008)
The article is to search for answers as to what changes have occurred in today’s Ashura mourning ceremonies to cause concerns amongst the majority of Muslims. After analyzing literary genres of epic, tragedy, and elegy, the conclusion is that one of the most significant changes was a shift from epic to tragedy in Ashura literary works in the previous centuries and then from tragedy to elegy in the previous years. Combining elegy with worldly love has created a certain type of literature whose mourning presents more a social than a religious function. The idea has been illustrated through samples from the available poems and dirges.